ANALISIS YURIDIS ATAS SERTIFIKAT FIDUSIA YANG HILANG BERKAITAN DENGAN PENDAFTARAN PERUBAHAN FIDUSIA PADA KANTOR PENDAFTARAN FIDUSIA DI MEDAN - DANNY AMBRITA (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. Hasballah Thaib2. Muhd Yamin3. Utary Maharany Barus The result of this study showed that what must be registered in fiduciary collateral is its bail bond which is based on the stipulation regulated in Article 12, Article 13 and Article 14 of Law No. 142/1999 on Fiduciary Collatreral. The registration of bail bond is included in the registration of fiduciary collateral change, fiduciary collateral certificate, and the change of fiduciary collateral certificate. Legal extension on the importance of fiduciary must be implemented by the fiduciary registration office by involving notary and banking because it is intended to provide legal protection for creditor. The protection provided by law for the creditor through the fiduciary collateral registration will ensure legal certainty and his/her rights.Keywords : Fiduciary Collateral, Fiduciary Collateral Registration, FiduciaryCollateral Certificate